Survey of Culturable Actinomycetes from Marine Macroorganisms and Mangrove Areas of Langkawi Islands - Geok Yuan Annie, Tan,; Christabel, Loni,; Ho Li, Sim,; binti Nik Abdul Aziz, Nik Zahirah; binti Syafri, , Sarini; Vikineswary, Sabaratnam, (Malaysian Journal of Science, 2005)
Fifty-two strains of actinomycetes isolated from bryozoan and marine sponges collected from the waters of Langkawi Islands were studied. The cell wall hydrolysates of twenty-two strains were found to contain the meso-diaminopimelic acid indicating that they are non-streptomycete strains. Furthermore, ninety-six strains of actinomycetes were isolated from soil samples collected from various mangrove areas during the first and second Langkawi Expeditions and forty-three of these strains have the meso-diaminopimelic acid in the cell wall hydrolysates. The strains were isolated using various selective isolation media for actinomycetes and several different pretreatment techniques. All the strains were further characterized by colour grouping. This study showed that the mangrove soils and marine organisms from Langkawi Islands hold relatively high diversity of non-streptomycete isolates that could be potential producers of novel bioactive compounds.